Kewajiban Menutup Aurat dalam Perspektif Al-Quran - Siti Purhasanah; Dindin Sofyan Abdullah; Ibnu Imam Al Ayyubi; Rifqi Rohmatulloh (Jurnal test, 2023)
Covering the genitals is not only a matter of wearing clothes that cover the genitals but to protect oneself, honoring and protecting oneself from something bad and unwanted. This study aims to find out the Al-Quran's perspective on the obligation to cover the genitals Muslims should know, especially women, how to cover the genitals properly according to Islamic law. The method used in this study is a descriptive qualitative research method with a literature study approach that refers to several commentary books to serve as research data sources and data collection techniques in the form of a study of commentary books on education. The focus of the research that will be raised is in the form of educational values ​​regarding the obligation to cover the private parts contained in the Qur'an. The data collection technique used in this study was the library research method, namely library research. The data analysis technique used in this research is the descriptive method. At present, many things are not well known by some Muslims who until now have not been moved to cover their genitals, even though covering their genitals is known to have many benefits and a positive impact on oneself.